DEKOMPOSISI TENAGA KERJA: SUMATERA UTARA - Dahlan Tampubolon (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
Eployment as an element of regional economic structured can be show held by decomposition method or shift-share analysis. This study used data employment from statistical of people welfare 1993-2003